Analisis Peran Risk Tolerance Dan Keberhasilan Diri Terhadap Motivasi Berwirausaha Pada Generasi Z - Sutrisno Sutrisno; Hendy Tannady; D.Yadi Heryadi; Reza Yonatan Hanata; Ahmad Gunawan (Journal of Economic, Bussines and Accounting (COSTING), 2023)
This study aims to analyze the effect of self-efficacy motivation and risk tolerance on students' desire to become entrepreneurs. There are two independent variables in this study, namely self-efficacy motivation and risk tolerance, and one dependent variable, namely entrepreneurial motivation. Researchers used quantitative methods and the sample used in this study amounted to 125 respondents who are undergraduate students studying at the Faculty of Business in Jakarta. The technique used in this research is accidental sampling. The research data were analyzed using Eviews 9. The results showed self-efficacy and risk tolerance had an influence on entrepreneurial motivation in students Faculty of Business in Jakarta.